Surface strain measurement using pulsed laser shearography with fibre-optic imaging bundles - Francis, Daniel (Cranfield University, 2008)
This thesis describes the development of a shearography instrument for the quantitative measurement of surface strain on dynamic test objects. Shearography is a non-contact, full-field interferometric speckle technique used for the measurement of displacement gradient. It is often used in industry for qualitative inspection of industrial components. To fully characterize the surface strain, a total of six components of displacement gradient are required. These can be measured using shearography instrumentation with at least three measurement channels. Phase measurements from each measurement channel are combined using a matrix transformation to produce the orthogonal displacement gradient measurements. The instrument presented in this thesis possesses four measurement channels consisting of four views of the object under investigation. Images from the four views are transported to the shearing interferometer using coherent fibre-optic imaging bundles. The signals from the four views are then spatially multiplexed onto the four quadrants of a CCD camera. The optical source is a frequency doubled, pulsed Nd:YAG laser which is used to effectively ‘freeze’ the motion of the dynamic object for the duration of the laser pulse. The optical phase difference between images recorded from two laser pulses is determined using the spatial carrier technique. This method involves introducing a carrier frequency into the recorded speckle pattern using a Mach-Zehnder interferometer. A Fourier transform is used to access the phase dependent spectral features, from which the phase distribution is calculated. The instrument is first validated through the measurement of two static test objects. The results of these measurements are compared with modelled data and with results from a multiple-illumination-direction shearography system using a continuous-wave laser. The instrument is then used to investigate two dynamic objects; a plate rotating at 610 rpm and a speaker cone vibrating at frequencies in the range of 1 – 5 kHz.